2007
DOI: 10.1002/lt.21280
|View full text |Cite
|
Sign up to set email alerts
|

Delayed-onset primary cytomegalovirus disease after liver transplantation

Abstract: Clinical practice guidelines recommend antiviral prophylaxis to cytomegalovirus (CMV) donor-positive/recipient-negative (Dϩ/RϪ) liver transplant recipients. We assessed the outcome of this strategy by determining the incidence, clinical features, and risk factors of CMV disease among CMV Dϩ/RϪ liver transplant recipients who received antiviral prophylaxis. Sixty-seven CMV Dϩ/RϪ liver transplant recipients (mean age Ϯ standard deviation: 49.5 Ϯ 11.4 years; 75% male) received oral ganciclovir [n ϭ 9 (13%)] or va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
132
6
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(154 citation statements)
references
References 29 publications
13
132
6
3
Order By: Relevance
“…In our analysis of 67 CMV D+/R li ver transplant recipients who recei ved 3 mo of oral ganciclovir and valganciclovir prophylaxis, the two year incidence of CMV disease was 29%. The incidence of delayedonset CMV disease was not significantly dif ferent between patients who recei ved oral ganciclovir or valganciclovir (22% vs 28%; P = 0.63) [3] . Thus, one out of every four CMV D+/R li ver transplant recipients will de velop CMV disease after cessation of anti viral prophylaxis.…”
Section: Delayed-and Late-onset CMV Diseasementioning
confidence: 82%
See 4 more Smart Citations
“…In our analysis of 67 CMV D+/R li ver transplant recipients who recei ved 3 mo of oral ganciclovir and valganciclovir prophylaxis, the two year incidence of CMV disease was 29%. The incidence of delayedonset CMV disease was not significantly dif ferent between patients who recei ved oral ganciclovir or valganciclovir (22% vs 28%; P = 0.63) [3] . Thus, one out of every four CMV D+/R li ver transplant recipients will de velop CMV disease after cessation of anti viral prophylaxis.…”
Section: Delayed-and Late-onset CMV Diseasementioning
confidence: 82%
“…The incidence is markedly reduced in li ver transplant recipients who recei ved 3 mo of prophylaxis with valganciclovir or oral ganciclovir. Re cent studies have reported CMV disease incidence rates of 12%30% in CMV D+/R, and < 10% in CMV R+ li ver transplant recipients who recei ved 3 mo of anti viral prophylaxis [3,4,9,1113] . The onset of disease in these patients occurs most commonly during first 3 mo after completing anti viral prophylaxis; hence, the term "delayedonset (also termed lateonset) CMV disease" to indicate that the on set has been delayed by anti viral prophylaxis (Figure 1) [3] .…”
Section: Direct CMV Effectsmentioning
confidence: 99%
See 3 more Smart Citations